Computer science in sport: research and practice (Routledge research in sport and exercise science, 2015)
Computers are a fundamentally important tool in sport science research, sports performance analysis and, increasingly, in coaching and education programmes in sport. This book defines the field of `sport informatics`, explaining how computer science can be used to solve sport-related problems, in both research and applied aspects.